Evaluation of analgesic, sympathetic and motor effects of 1% and 2% lidocaine administered epidurally in dogs undergoing ovariohysterectomy - Nejamkin, Pablo (2020)
Objective: To compare, versus a control, the sensory, sympathetic and motor blockade of lidocaine 1% and 2% administered epidurally in bitches undergoing ovariohysterectomy. Study design: Randomized, blinded, controlled clinical trial. Animals: A total of 24 mixed-breed intact female dogs. Methods: All dogs were administered dexmedetomidine, tramadol and meloxicam prior to general anesthesia with midazolam–propofol and isoflurane. Animals were randomly assigned for an epidural injection of lidocaine 1% (0.4 mL kg−1; group L1), lidocaine 2% (0.4 mL kg−1; group L2) or no injection (group CONTROL). Heart rate (HR), respiratory rate (fR), end-tidal partial pressure of carbon dioxide (PE′CO2), and invasive systolic (SAP), mean (MAP) and diastolic (DAP) arterial pressures were recorded every 5 minutes. Increases in physiological variables were treated with fentanyl (3 μg kg−1) intravenously (IV). Phenylephrine (1 μg kg−1) was administered IV when MAP was <60 mmHg. Postoperative pain [Glasgow Composite Pain Score – Short Form (GCPS–SF)] and return of normal ambulation were recorded at 1, 2, 3, 4 and 6 hours after extubation. Results: There were no differences over time or among groups for HR, fR, PE′CO2 and SAP. MAP and DAP were lower in epidural groups than in CONTROL (p = 0.0146 and 0.0047, respectively). There was no difference in the use of phenylephrine boluses. More fentanyl was administered in CONTROL than in L1 and L2 (p = 0.011). GCPS–SF was lower for L2 than for CONTROL, and lower in L1 than in both other groups (p = 0.001). Time to ambulation was 2 (1–2) hours in L1 and 3 (2–4) hours in L2 (p = 0.004). Conclusions and clinical relevance: Epidural administration of lidocaine (0.4 mL kg−1) reduced fentanyl requirements and lowered MAP and DAP. Time to ambulation decreased and postoperative pain scores were improved by use of 1% lidocaine compared with 2% lidocaine.